A Role for Bose-Einstein Condensation in Astrophysics - Barry W. Ninham; Iver Brevik; Oleksandr I. Malyi; Mathias Boström (Substantia, 2023)
We revive a 60-year-old idea that might explain a remarkable new observation of a periodic low-frequency radio emission from a source at galactic distances (GLEAM-X J162759.5-523504.3). It derives from the observation that a high-density high-temperature charged boson plasma is a superconducting superfluid with a Meissner effect.